EMERGENCY RESPONSE TRAINING FOR FLOOD TIDES: ENHANCING PREPAREDNESS OF THE KEDUNG COWEK COASTAL COMMUNITY, SURABAYA - Pujo Semedi, Bambang; Kriswidiyatomo, Prihatma; Surgean Veterini, Anna; Sumartono Waloejo, Christrijogo; Abbas, Kun Arifi; Perdhana, Fajar; Mutiar, Airi; Rahmanto, Ilham; Rifqi, Muhammad Andika (Universitas Airlangga, 2025)
Tidal flooding is one of the hydrometeorological disasters caused by extreme weather that frequently affects the coastal area of Kampung Nelayan, Kedung Cowek Subdistrict, Surabaya City. Based on risk analysis, the community’s level of knowledge and attitude in responding to disasters plays a crucial role in mitigation efforts; thus, training and the initiation of a disaster response community are necessary. This community service program aimed to provide theoretical education and practical training on Basic Life Support (BLS), accompanied by the initiation of a fishermen disaster response community for 35 people of Kampung Nelayan, Kedung Cowek. The program was conducted at the Kedung Cowek Village Hall and included: (1) BLS education through presentations, (2) practical simulation of chest compressions using a mannequin and evacuation with a stretcher, (3) distribution of personal protective equipment for fishermen, and (4) the establishment of a disaster response community. Improvements in knowledge and attitude were measured using pre- and post-test questionnaires and analyzed with the Wilcoxon Signed-Rank test in SPSS with significance level at 0,05. The results showed a significant increase in knowledge (68.66 ± 21.68 vs 95.33 ± 2.61) and attitude (50.71 ± 14.24 vs 64.95 ± 3.27) (p < 0.01). The initiation of a disaster response coastal community is expected to strengthen the tidal flood management system through adequate BLS provision, so the capacity and resilience of coastal communities are sustainably maintained.